GEOMETRIC ASPECTS OF THE GEDHE KAUMAN MOSQUE IN YOGYAKARTA - Putri, Elina Eka; Putri, Odhistya Maharani (Ethnomathematics Journal, 2024)
This research aims to analyze ethnomathematics in a mosque named Gedhe Kauman in Yogyakarta. The ethnomathematics studied is related to the mathematical concepts of area and perimeter of two dimensional shapes. This research is qualitative research with an ethnographic approach. The data source in this research is the result of direct observation and documentation by the researcher. Data collection techniques were carried out by observing and documenting mosque buildings. Testing the validity of the data was carried out using technical triangulation. The subject of this research is the historic building of the Gedhe Kauman Mosque. Based on the research results, it was found that the Mosque building is quite closely related to ethnomathematics learning resource. This is proven by the presence of geometric elements in the structure and contents of the building that have easyly reognized patterns. The geometric shapes found are squares, rectangles, circles, triangles and trapezoids. These plane shapes can be integrated into the mathematical concepts of perimeter and area for learning elementary mathematics. This instructional approach might evoke student's disposition towards mathematics.